The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1590/s0100-29452008000400025
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de bananeiras cultivadas em ambiente protegido sob efeito do paclobutrazol aplicado nas folhas

Abstract: RESUMO -Com o objetivo avaliar os efeitos do paclobutrazol aplicado via foliar sobre o desenvolvimento de bananeiras cultivadas em ambiente protegido, durante o primeiro ciclo de produção, foi instalado um experimento seguindo o esquema fatorial, com cinco doses do produto (0; 0,5; 1,0; 1,5 e 2,0 g de i.a. planta -1 ), combinados com duas cultivares, 'Prata-Anã' e 'FHIA 01'. O paclobutrazol não influenciou em características como o número de dias do plantio ao florescimento e área foliar total. Contudo houve u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…For pseudostem diameter, this study revealed that both paclobutrazol and mepiquat chloride generated a reduction in the thickness of the pseudostem when compared to the control (Tab 1). This result is similar to that obtained by Maia et al (2008), who submitted two banana cultivars to treatments with paclobutrazol via foliar spraying and obtained a reduction in the diameter of the pseudostem.…”
Section: Resultssupporting
confidence: 90%
“…For pseudostem diameter, this study revealed that both paclobutrazol and mepiquat chloride generated a reduction in the thickness of the pseudostem when compared to the control (Tab 1). This result is similar to that obtained by Maia et al (2008), who submitted two banana cultivars to treatments with paclobutrazol via foliar spraying and obtained a reduction in the diameter of the pseudostem.…”
Section: Resultssupporting
confidence: 90%
“…This indicates that, when the mother plant is felled at harvest time, the plant will regrow, guaranteeing the longevity of the crop in the area (Bolfanaria et al, 2014). In addition to its importance for the longevity of the plantation, surplus shoots can also be transferred to new areas by the farmer (Maia et al, 2008).…”
Section: Resultsmentioning
confidence: 99%